2018
DOI: 10.1002/1873-3468.13289
|View full text |Cite
|
Sign up to set email alerts
|

Functional and solution structure studies of amino sugar deacetylase and deaminase enzymes from Staphylococcus aureus

Abstract: N‐Acetylglucosamine‐6‐phosphate deacetylase (NagA) and glucosamine‐6‐phosphate deaminase (NagB) are branch point enzymes that direct amino sugars into different pathways. For Staphylococcus aureus NagA, analytical ultracentrifugation and small‐angle X‐ray scattering data demonstrate that it is an asymmetric dimer in solution. Initial rate experiments show hysteresis, which may be related to pathway regulation, and kinetic parameters similar to other bacterial isozymes. The enzyme binds two Zn2+ ions and is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…As shown in Figure 3A Figure 3B). The binding motif at this region, 8 GxGxxG 13 confers cofactor specificity for NAD(H) over NADP(H). 56 Specifically, the cofactor was recognized by the side chains of residues F12, D33, N36, N70, H73, K91, W160, and K161, through an interaction that was mediated by an ordered water molecule ( Figure S5).…”
Section: Cofactor Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3A Figure 3B). The binding motif at this region, 8 GxGxxG 13 confers cofactor specificity for NAD(H) over NADP(H). 56 Specifically, the cofactor was recognized by the side chains of residues F12, D33, N36, N70, H73, K91, W160, and K161, through an interaction that was mediated by an ordered water molecule ( Figure S5).…”
Section: Cofactor Bindingmentioning
confidence: 99%
“…5 In addition, the catabolism of sialic acids yield precursors for peptidoglycan biosynthesis, such as N-acetylglucosamine. 7,8 Lastly, some bacteria can decorate their cell surfaces with host-derived sialic acids to camouflage themselves against the host innate immune system. 1,9 Given the accessibility of sialic acids in mucus rich environments, their utilization offers pathogenic bacteria and commensals, such as Escherichia coli, a competitive advantage to colonize and persist within the human host.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover in [19] authors utilize Fourier transform infrared spectroscopy to investigate kinetics of a series of five DNA sequences to clarify the commonly observed physical processes. As a result of our study, it was shown that SMCs in the composition of drugs undergo hysteresis phenomena, exhibiting long-period conformational mobility, which probably should be taken into account when the drug is tested in vitro [8,12]. Hysteresis phenomena in water-lactose SMCs illustrated by the results of two spectral methods of analysis are most likely associated with the influence of environmental factors such as variations in relative humidity, temperature, background variations in the level of natural radioactivity, including the flux of thermal neutrons [20,21], which can be a source of energy for conformational rearrangements [22,23].…”
Section: Discussionmentioning
confidence: 76%
“…The observed kinetic transitions suggest the existence of a free energy barrier between the states of the supramolecular structure. The process can be compared with the kinetic trapping phenomenon, well studied, and described for protein molecules, associated with conformational differences between the long-lived transitional and stable final states [7,8].…”
Section: Fig 1: the Formation Of A Water-lactose Complex (Smc) And Rmentioning
confidence: 99%
“…These TRAPs transport sialic acids, a family of nine-carbon amino sugars, the most common of which is N- acetylneuraminic acid ( North et al, 2018 ). The focus on these systems is due to the growing interest in the role of sialic acid as an important nutrient source for pathogenic bacteria in vivo ( North et al, 2016 ; North et al, 2018 ; Wahlgren et al, 2018 ; Davies et al, 2019 ; Coombes et al, 2020 ; Horne et al, 2021 ). Electrochemical studies have been used to characterise the transport of sialic acid through the H. influenzae SiaPQM system ( Mulligan et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%